Sprawozdanie z przebiegu Ogólnopolskiej Konferencji „Praktyki wobec zwierząt w XXI wieku – hodowla, etyka, śmierć i przeznaczenie” - Białas, Piotr (Zoophilologica. Polish Journal of Animal Studies, 2017)
Piotr Białas's report on the conference titled "Practices concerning animals in the 21st century - breeding, ethics, death and fate" organized in Poznań by the Adam Mickiewicz University (UAM) and Karol Marcinkowski Medical University (UMP) along with the "Otwarte Klatki" ("Open Cages") Association at the turn of September 2016.